Avaliação do impacto da implantação do método de revisão rápida de 100% na garantia da qualidade dos exames citopatológicos do colo do útero - Magalhães, Juliana Cristina (2016)
Background: One of the big problems that cytopathology laboratories face in their routine are false negative (FN). A way to minimize these FN results and increase the Pap smears sensitivity is the implementation of methods of internal quality control. Objective: To evaluate the impact of the implementation of 100% rapid review method (RR 100%) in the Pap smears quality assurance, checking the cytopathology results, the FN results detection frequency and quality indicators. Methods: Cross-sectional study whose sample was composed of the number of tests performed in the years 2004 (4.943) and 2013 (6.278) totaling 11,221 tests, using data from the Information System Cervical Cancer. The quality internal control information were collected from the archives of the center of clinical analyses. Were evaluated the variables: cytopathology results, FN results’ detection frequency and quality indicators [positivity rate, percentage of tests compatible with atypical squamous among abnormal tests (%ASC/abnormal tests), atypical squamous/squamous intraepithelial lesion ratio (ASC/SIL) and percentage of tests compatible with high-grade squamous intraepithelial lesion (%HSIL/satisfactory)]. The variables were analyzed in the year that was implemented the RR 100%, 2004, and after ten years of implementation, 2013, and were analyzed descriptively through the absolute and relative frequencies. To check the impact of the implementation of RR 100% was used chi-square test with 5% significance level. Results: From the 4,943 cytopathology tests performed in 2004, 4,818 (97,47%) were satisfactory and 125 (2,53%) were unsatisfactory. In the year 2013, 6,278 tests were analyzed, 6,050 (96,37%) satisfactory and 228 (3,63%) unsatisfactory for analysis. The borderline atypia, atypical squamous cells of undetermined significance (ASC-US) and atypical squamous cells, cannot exclude a high-grade squamous intraepithelial lesion (ASC-H) increased from 1.00% and 0.10%, respectively, in 2004 to 2.93% and 3.37%, respectively, in 2013. High-grade squamous intraepithelial lesion (HSIL) increased from 0.64% in 2004 to 4.55% in 2013. From the 275 tests classified as HSIL in 2013, 20 (7,27%) were identified by the RR 100%. Thirty (16,95%) of 177 ASC-US, 37 (18,14%) of 204 ASC-H and 13 (8,07%) of 161 low-grade squamous intraepithelial lesion, were also identified through RR 100%. There was a significant increase (p ≤ 0.05) in the FN results detection frequency categorized as ASC-US and ASC-H and as HSIL after ten years of implementation of the RR 100%. About the quality indicators, the positivity rate increased from 3.9% to 13.7%. The %ASC/abnormal tests and ASC/SIL increased from 28.2% and 0.4 respectively, to 45.8%, and 0.9, respectively. The %HSIL/satisfactory increased from 0.6% to 4.5%. Conclusions: the results of this study showed that RR 100% method is efficient to ensure the Pap smears quality, with an improvement in the detection of atypical and precursor lesions, and in the quality indicators.